A stone stele with the depiction of a Linga and a devotee - Temples of India Project Team (Jio Institute, 2024)
A stone stele is placed near the foundation of the subsidiary shrine (II) on the left side corner near the entrance of the Mahakal shrine. The stele depicts a Shiva Linga and a devotee, who is shown seated and worshiping the Linga. The Linga has a pedestal, yoni bhaga, which holds the Linga. The surface of the stele is quite weathered so the details are not clear.